Phosphorus dynamics in an ultisol - Smitha M S (Department of Soil Science and Agricultural Chemistry, College of Horticulture, 2005)
A pot culture experiment was carried out at Radiotracer laboratory of College of Horticulture, Vellanikkara, using laterite soil (Ultisol), from the main campus of Kerala Agricultural University with the objectives to trace the fate of fertilizer P and to study the dynamics of P by the addition of amendments. The experiment included 13 treatments of three levels of P and four amendments and an absolute control. Amendments were added to the respective treatments and kept for wetting and drying cycles for two weeks 32P labelled KH2PO4 (32P @ 0.4mCig-1 P) was added as per the treatments. Seeds of cowpea @ 3 seeds pot -1 were sown. Application of Phosphorus at different levels significantly contributed to available P status different P fractions i.e. non occluded Al-P and Fe-P, P sorbed by carbonate, occluded P and Ca-P in a linear fashion at all the stages of crop growth i.e. just before sowing, flowering and harvesting. The amendments also contributed to the above pools. Among the amendments Pongamia leaves was found to have better influence in contributing to the above pools except for Ca-P, where lime was found to have a better influence. This was supported by the data on plant P content, where the increasing levels of P and amendments improved the plant P content at 15 DAS, flowering and at harvest. Further Ca-P fraction was dominantly contributing to the available P suggesting that applied P might get transformed to non occluded Al-P and Fe-P, occluded P as well as P sorbed by carbonate, which might be slowly transformed to Ca-P fraction probably Ca (H2PO4)2, the soluble form which is contributing to available P. It was observed that, non occluded Al-P and Fe-P was contributing to plant P as time proceeded due to solubilisation of this fraction. Application of P at increasing level and amendment significantly increased the dry weight of pods and haulm. Radioactive 32P labelled with the applied phosphorus could be traced out in the available pools and fractions of P only at just before sowing, flowering. Percentage of P derived from applied P were the highest for higher level of P and amendment sodium silicate.